SPECIES COMPOSITION OF GLASS EELS RECRUITING TO THE PALU RIVER - Ndobe, Samliok; Serdiati, Novalina; Moore, Abigail (Journal of Agroecology, 2015)
Indonesia is widely recognised as the centre of freshwater eel diversity. The recruitment of tropical glass eels generally occurs in multi-species schools. Identification of species present and recruitment patterns at regional and watershed scales are necessary to conserve eel biodiversity and manage eel populations sustainably. Data on eel taxonomy, phylogeography and biogeography are still limited in many areas. Research over the period 2009–2012 aimed to: 1) determine the species composition of glass eels recruiting to Palu River, flowing into Palu Bay on the Central Sulawesi Makassar Straits coastline; and 2) to develop a suitable method for live glass eel identification. Sampling was carried out over 29 months: January–April 2009, May–November 2010, April–December 2011 and March–November 2012. Two species were positively identified using the ano-dorsal vertebrae count (ADV) method, Anguilla marmorata and A.bicolor pacifica. The presence of other species (possibly one to three species) is important from conservation and biodiversity aspects. Temporal variations in species composition, with no apparent consistent seasonal or annual pattern raise questions requiring a multi-disciplinary approach.